2013
DOI: 10.1007/s10152-013-0365-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and karyotypic differentiation in Caranx lugubris (Perciformes: Carangidae) in the St. Peter and St. Paul Archipelago, mid-Atlantic Ridge

Abstract: Isolated oceanic islands constitute interesting model systems for the study of colonization processes, as several climatic and oceanographic phenomena have played an important role in the history of the marine ichthyofauna. The present study describes the presence of two morphotypes of Caranx lugubris, in the St. Peter and St. Paul Archipelago located in the mid-Atlantic. Morphotypes were compared in regard to their morphological and cytogenetic patterns, using C-banding, Ag-NORs, staining with CMA 3 / DAPI fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Beyond the differences found between basal and derived orders in fish phylogeny, the tendency towards chromosome acrocentrization seems to occur even within groups at the family level. For example, the ancestral karyotype reconstruction analysis performed in the family Carangidae has shown that although the diploid number 2n = 48 is conserved in the family, karyotypes with higher numbers of biarmed chromosomes (m/sm) are predominant in basal clades, whereas a higher proportion of acrocentric chromosomes with a decreasing tendency or complete elimination of biarmed chromosomes is observed in most derivative species [30]. In the case of Lebiasina , which is considered basal in the family, the presence of biarmed chromosomes must represent a basal condition for the family, a fact that is also reinforced by the absence of any ITS signal on their chromosomes (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the differences found between basal and derived orders in fish phylogeny, the tendency towards chromosome acrocentrization seems to occur even within groups at the family level. For example, the ancestral karyotype reconstruction analysis performed in the family Carangidae has shown that although the diploid number 2n = 48 is conserved in the family, karyotypes with higher numbers of biarmed chromosomes (m/sm) are predominant in basal clades, whereas a higher proportion of acrocentric chromosomes with a decreasing tendency or complete elimination of biarmed chromosomes is observed in most derivative species [30]. In the case of Lebiasina , which is considered basal in the family, the presence of biarmed chromosomes must represent a basal condition for the family, a fact that is also reinforced by the absence of any ITS signal on their chromosomes (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Similar phylogeographic breaks to those reported here in E . vomerinus , particularly the break separating the North group, were also detected in other reef fish species, such as Chromis multilineata (Pomacentridae) and Caranx lugrubis (Carangidae) [ 56 , 57 ], suggesting that these phylogeographic barriers might work as a useful biogeographic hypothesis for co-distributed species. Together, our results suggest significant evolutionary diversification within E .…”
Section: Discussionmentioning
confidence: 99%
“…In groups of fish with conserved chromosomal characteristics, the mapping of 18 and 5S sequences using dual-color FISH, as used for C. bartholomei, C. latus, and C. lugubris allows analysis of karyotype evolution, rearrangements involved in diversification, and discrimination of species or populations (Accioly et al, 2012;Jacobina et al, 2013). The presence of 18S rDNA sites on the same homeolog pair (pair 1) and 5S rDNA sites located at the same position (short arm) of pair 15 in C. bartholomei and C. latus reinforce the conservation and phylogenetic proximity among the species in these 2 genera (Carangoides and Caranx), which are considered by some authors to belong to the same genus (Smith-Vaniz, 1984;Reed et al, 2002).…”
Section: Discussionmentioning
confidence: 99%